Development of AITC‐induced dermal blood flow as a translational in vivo biomarker of TRPA1 activity in human and rodent skin. Issue 1 (2nd June 2020) - Joseph, Victory; Yang, Xiaoying; Gao, Simon S.; Elstrott, Justin; Weimer, Robby M.; Theess, Wiebke; Thrasher, Cory; Singh, Nand; Lin, Joseph; Bauer, Rebecca N.
Abstract : Background and Purpose: Develop a translational assay of Transient Receptor Potential Ankyrin 1 (TRPA1) activity for use as a preclinical and clinical biomarker. Experimental Approach: Allyl isothiocyanate (AITC), capsaicin or citric acid were applied to ears of wildtype and Trpa1 ‐knock out ( Trpa1 KO ) rats, and changes in dermal blood flow (DBF) were measured by laser speckle contrast imaging. In humans, the DBF, pain and itch responses to 5‐20% AITC applied to the forearm were measured and safety was evaluated. Reproducibility of the DBF, pain and itch responses to topically applied 10% and 15% AITC were assessed at two visits separated by 13‐15 days. DBF changes were summarized at 5‐minute intervals as areas under the curve (AUC) and maxima. Intraclass correlation coefficient (ICC) was calculated to assess arm‐arm and period‐period reproducibility. Key Results: AITC‐ and citric acid‐induced DBF were significantly reduced in Trpa1 KO rats compared to wildtype (90 ± 2% and 65 ± 11% reduction, respectively), whereas capsaicin response did not differ. In humans, each AITC concentration significantly increased DBF compared to vehicle with the maximal increase occurring 5 minutes post application. Ten percent and 15% AITC were selected as safe and effective stimuli. AUC from 0 to 5 minutes was the most reproducible metric of AITC‐induced DBF across arms (ICC = 0.92) and periods (ICC = 0.85). Subject‐reported pain was more reproducible than itch across visits (ICC = 0.76 vs 0.17, respectively). Conclusion and Implications: AITC‐induced DBF is a suitable target engagement biomarker of TRPA1 activity for preclinical and clinical studies of TRPA1 antagonists.